THE CONTRIBUTION OF SELF-CONTROL TO STUDENTS’ COMPLIANCE WITH SCHOOL REGULATION: A CORRELATION ANALYSIS - Barep H Surya P; Ageng Triyono (JURNAL TARBIYAH, 2025)
Student discipline is a key factor in creating an effective learning climate in schools; however, violations of school regulations are still frequently observed, often due to weak self-control among adolescents. This study aims to examine the relationship between self-control and adherence to school rules among twelfth-grade students. A quantitative approach with a correlational design was employed. The sample comprised 102 students randomly selected from a population of 239. Data were collected using a closed-ended, Likert-scale questionnaire that had been validated and proven reliable. Data analysis was conducted using Pearson product-moment correlation with the assistance of SPSS software. The results revealed a significant positive relationship between self-control and student discipline in adhering to school rules (r = 0.557, p < 0.05), with self-control contributing 31.10% to the variance in student discipline. These findings underscore the importance of strengthening self-control development programs through counseling services and habituation of discipline in schools as strategic efforts to improve students’ compliance with school regulations.